Análisis de las productoras de contenido digital de ficción de las provincias de Loja y Zamora Chinchipe, el periodo mayo-agosto 2023 - Beltran Ortega, Gabriela Patricia (2024)
For audiovisual production companies the scenario is changing, traditionally the production is directed to traditional media such as television or cinema, the evolution of technology and consumer trends have led to the generation of audiovisual content within social networks, this has led to a change in the way an audiovisual company is constituted, the administrative structure and the format of content creation for Internet platforms. This work aimed to understand the dynamics of digital production companies of fiction content in the provinces of Loja and Zamora Chinchipe: to identify their production dynamics, compare their themes and the quality of the content they produce, in order to understand the audiovisual imaginary in which many communication professionals currently operate. In accordance with these objectives, an observation in networks and bibliographic documents was carried out to identify the different production companies; this search was complemented with semi-structured interviews to managers of the production companies, the answers to which allowed us to determine their production structure. Along the same lines, an observation sheet was used to determine the similarities and differences in the contents, structure and themes of the production companies. The results showed that both the production dynamics and the organizational structure of these companies are simplified and the recurring themes deal with social problems of a melodramatic nature with which their audience identifies, in addition to generating characters that later become a trend and attract followers from personal profiles, increasing the visualizations of their products. Keywords: audiovisual company; audiovisual production companies; digital production company; fiction; organizational structure.